Profile of Clinical, Radiological and Laboratory Pattern in TB-HIV Coinfection in National Infection Centre of Indonesia - Rosamarlina, Rosamarlina; Hatta, Mochammad; Murtiani, Farida; Widiantari, Aninda Dinar (Universitas Wijaya Kusuma Surabaya, 2024)
Background: The study aims to map TB (Tuberculosis) – HIV (Human Immunodeficiency Virus) patients based on clinical, radiological, and laboratory patterns. Objective: This study is expected to provide previous research investigating radiologic and laboratory examinations in TB-HIV patients. Method: We conducted a cross-sectional study based on medical records of TB-HIV patients at RSPI Sulianti Saroso from January 2004 - March 2017. Samples were 240 TB-HIV patients from a population of 1014 People Living with HIV/AIDS (PLWHA). Inclusion criteria were PLWHA, aged over 18 years, diagnosed with TB with completed medical record status. Result: Characteristics of the majority of patients were in the productive age group (99.2%) with an average age of 33 years and male sex (78%). The main symptom is cough (91.7%) and cough with phlegm (59.1%). Most patients (83.37%) have not received ART (Anti-Retroviral Therapy). Pulmonary physical examination showed that most patients had Ronchi (95.8%) while others got wheezing (5%). Laboratory tests revealed an initial CD4 cell count of 71.6 cells/ml and a negative Acid-Fast Bacillus (AFB) smear (59.2%). The patient's radiology was mainly with an infiltrate (82.5%); most infiltrate was presented in apex (52.4%). Conclusion: The majority of TB-HIV coinfected patients are young males, presenting with common TB symptoms, low CD4 counts, and negative AFB smears, complicating diagnosis. Radiological findings frequently show infiltrates, particularly in the apex. These findings emphasize the importance of early diagnosis and ART initiation to improve outcomes in TB-HIV coinfected patients